Readiness of public libraries to deliver information literacy instruction to school children: a case study of a City of Cape Town public library - Notshokovu, Cwayita (Department of Knowledge and Information Stewardship, 2025)
Information literacy (IL) is an integral part of lifelong learning. IL instruction is accepted internationally as the specific mission of school libraries. However, in South Africa, there are few schools that have functional school libraries, and so it is unrealistic to put the IL instruction responsibility on school libraries. Therefore, public libraries need to step in and close the IL gap. However, it is not clear how well equipped public libraries are for this role. To examine the problem above, the main objective of this study was to investigate the readiness of public libraries to offer IL support to school learners. The Big6 model guided data collection in this study in terms of the formulation of the interview questions for librarians, and the observations guide. Under the interpretive paradigm, this study employed a qualitative research approach with a case study design. The case is that of a public library referred to as the Library in this study. The Library is an example of one library in the City of Cape Town and the researcher was interested in providing an in-depth study of this library with regards to IL instruction support for school learners. One of the reasons it was chosen is because there are a number of schools in the area in which it is situated. The populations for the study were the public librarians working at the Library and schoolteachers from the surrounding primary and high schools. There was no sampling required for public librarians because their population was manageable. However, non-probability sampling was employed for schoolteachers, coupled with purposive sampling. The data from the public librarians were collected through semi structured interviews and observations, while the data from the schoolteachers were collected through semi-structured interviews only. Data were analysed manually. Findings indicated that the majority of the librarians in the study have a combination of work experience and LIS qualifications (though some were obtained a long time ago), which contributes positively to their readiness to teach IL. The findings of the study revealed that there is no sustained programme that is explicitly referred to as IL at the Library. However, librarians at the Library offer IL support to school learners and IL support for school learners is embedded in various library programmes, such as library orientation, digital literacy, storytelling, and the homework assistance, reading and holiday programmes. The findings also showed that the librarians in the study generally have a positive attitude towards teaching IL to school learners, although they acknowledged that they are not teachers by profession. Furthermore, it was revealed that while there was no collaboration between the Library and one of the primary schools in the study, the Library does collaborate with some of the teachers from the other schools. It is hoped that this study will contribute to the body of literature, particularly that of information literacy education for school children in public libraries.